International disability rights advocacy : languages of moral knowledge and institutional critique - Pateisky, Daniel (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book provides insight into the globally interlinked disability rights community and its political efforts today. By analysing what disability rights activism contributes to a global power apparatus of disability-related knowledge, it demonstrates how disability advocacy influences the way we categorise, classify, distribute, manipulate, and therefore transform knowledge. Unpacking the mutually constitutive relations between (practical) moral knowledge of international disability advocates and (formal) disability rights norms that are codified in international treaties such as the UN Convention on the Rights of Persons with Disabilities (CRPD), the disability rights movement is shown to be largely critical of statements that streamline it. At the same time, cross-cultural disability rights advocacy requires images of uniformity to stabilise its global legitimacy among international stakeholders and retain a common meta-code that visibly identifies its aims. As an epistemic community, disability rights advocates simultaneously rely on and contest the authority of international human rights infrastructure and its language. Proving that disability rights advocates contribute immensely to a global culture that standardises what is considered morally and legally 'right' and 'wrong', thereby shaping the body and the body politic, this book will be of interest to all scholars and students of disability studies, sociology of knowledge, legal and linguistic anthropology, social inequality and social movements"--
Theory with unstable referents -- Methodical approach -- Reflecting languages and symbols -- Paradigmatic lines and actor relationships -- Reconciling multiple knowledges -- Categorising and explaining as knowledge change -- Advocacy knowledge as political-legal intervention -- Final discussion -- Addendum.
OCLC-licensed vendor bibliographic record.
Keywords: Convention on the Rights of Persons with Disabilities and Optional Protocol -- (2007 March 30); People with disabilities -- Legal status, laws, etc; Legal assistance to people with disabilities; People with disabilities -- Moral and ethical aspects; SOCIAL SCIENCE / Handicapped; LAW / Disability; POLITICAL SCIENCE / Public Policy / Social Services & Welfare